Peer victimization, depression, and non-suicidal self-injury among Chinese adolescents: the moderating role of the 5-HTR2A gene rs6313 polymorphism - Meijin Li; Huahua Wang; Jingjing Li; Yuting Deng; Chengfu Yu (Child and Adolescent Psychiatry and Mental Health, 2022)
Abstract Background Peer victimization is a crucial risk predictor for adolescent non-suicidal self-injury (NSSI). However, adolescent NSSI reactions to peer victimization exhibit large individual differences. This study explored whether depression mediated the association between peer victimization and adolescent NSSI, and whether this mediating path was moderated by the 5-HTR2A gene rs6313 polymorphism. Methods A total of 667 adolescents (Mean age = 12.81, SD = 0.48) completed questionnaires regarding peer victimization, depression, and NSSI. Genomic DNA was extracted from saliva and buccal cells from each participant. Results The results showed that the positive relation between peer victimization and adolescent NSSI was mediated by depression. Moreover, the triple interaction between peer victimization, rs6313 polymorphism, and gender on adolescent depression was significant. And the triple interaction between depression, rs6313 polymorphism, and gender on adolescent NSSI was also significant. Specifically, the risk effect of peer victimization on adolescent NSSI through increased depression was stronger for female adolescents with CC genotype than for female adolescents with CT or TT genotype, and male adolescents with CT or TT genotype. However, the indirect effect was nonsignificant for male adolescents with CC genotype. Conclusions These findings promote the etiological understanding of adolescent NSSI, highlighting the mediating and moderating effect between peer victimization and NSSI, and adding evidence supporting the relationship between the 5-HTR2A gene rs6313 polymorphism, depression and adolescent NSSI.